Learning From Vitamin B12‐Mediated Reactions: Cobalt(III)−Carbon‐Assisted Catalytic C−H Difluoroacylation of (Hetero)Arenes through Controlled‐Potential Electrolysis. Issue 16 (3rd April 2019) - Hossain, Md. Jakir; Ono, Toshikazu; Yano, Yoshio; Hisaeda, Yoshio
Abstract: The synthesis of difluoromethylated (CF2 R) (R=H, alkyl/aryl, CO2 R, etc.) compounds has received considerable attention in recent years. In this study, the cobalt(III)−carbon‐mediated catalytic C−H difluoroacylation of unactivated arenes and heteroarenes using BrCF2 CO2 Et is reported. This catalytic cycle is based on a valence change of the cobalt catalyst, a naturally derived vitamin B12 derivative, driven by controlled‐potential electrolysis at −0.8 V vs. Ag/AgCl under visible‐light irradiation in dimethyl sulfoxide. A broad substrate scope is demonstrated, and two compounds were characterized according to their X‐ray crystal structures. Mechanistic studies showed that the reaction proceeds through a radical pathway mediated by homolytic cleavage of the cobalt(III)–carbon bond. A turnover number of more than 100 was observed, owing to the inherent stability of the vitamin B12 framework. This naturally derived catalytic system has potential applications in medicinal chemistry and materials science. Abstract : Radical discovery : A naturally derived vitamin B12, which has a cobalt ion in the corrin‐ring, acts as a good catalyst for difluoroacylation reaction of arenes and heteroarenes driven by controlled‐potential electrolysis at −0.8 V vs. Ag/AgCl under photoirradiation in DMSO. The reaction proceeds through a radical pathway mediated by homolytic cleavage of the cobalt(III)−carbon bond.